2010
DOI: 10.1007/s00213-010-1845-4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of intravenous nicotine self-administration by opioid receptor agonist and antagonists in rats

Abstract: These findings suggest endogenous opioids are crucial in mediating the reinforcing effects of nicotine and that the mu-opioid receptor subtype may represent a potential target for selectively reducing nicotine-taking behaviour as part of a pharmacological approach to develop smoking cessation aids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 49 publications
5
33
0
Order By: Relevance
“…The present findings offer support for previous studies which demonstrated a specific role for the KOR system in drug seeking, particularly, nicotine seeking (Al-Hasani et al, 2013; Ismayilova and Shoaib, 2010; Jackson et al, 2010, 2013; Smith et al, 2012). We found that activation of KORs with U50,488 dose dependently reinstated nicotine seeking, an effect which was attenuated by the KOR antagonist nor-BNI.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings offer support for previous studies which demonstrated a specific role for the KOR system in drug seeking, particularly, nicotine seeking (Al-Hasani et al, 2013; Ismayilova and Shoaib, 2010; Jackson et al, 2010, 2013; Smith et al, 2012). We found that activation of KORs with U50,488 dose dependently reinstated nicotine seeking, an effect which was attenuated by the KOR antagonist nor-BNI.…”
Section: Discussionsupporting
confidence: 91%
“…In the hypothalamus, injection of the ENK analog [D-Ala(2),N-MePhe(4),Gly(5)-ol]-Enkephalin (DAMGO) in the PVN or of OX in the PFLH stimulates the drinking of ethanol and consumption of a high-fat diet (Clegg et al, 2002;Naleid et al, 2007;Morganstern et al, 2010a), with opposite effects produced by the receptor antagonists (Lawrence et al, 2006;Naleid et al, 2007;Moorman and Aston-Jones, 2009;, and administration of DAMGO directly in the CeA also increases consumption of a fat-rich diet ). In addition, peripheral administration of an OX receptor 1 antagonist or of opioid antagonists is found to reduce the self-administration of nicotine (Corrigall et al, 2002;Hollander et al, 2008;Ismayilova and Shoaib, 2010;LeSage et al, 2010). Although yet to be studied with nicotine self-administration, MCH when centrally injected increases the consumption of ethanol (Duncan et al, 2005;Morganstern et al, 2011) and is endogenously elevated in the PFLH of rats prone to overconsuming fat (Morganstern et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Self-administration of nicotine is reduced by hypothalamic administration of an OX receptor 1 antagonist (LeSage et al, 2010) and peripheral opioid antagonist (Ismayilova and Shoaib, 2010), and although yet to be studied with nicotine, central injection of MCH increases the consumption of ethanol (Duncan et al, 2005;Morganstern et al, 2011). Conversely, administration of nicotine stimulates expression of OX in the perifornical lateral hypothalamus (PFLH) and ENK in the hypothalamic paraventricular nucleus (PVN) and central nucleus of the amygdala (CeA) (Houdi et al, 1998;Loughlin et al, 2006) and OX mRNA is increased by chronic nicotine (Houdi et al, 1998;Kane et al, 2000). If these peptides do in fact have a role in potentiating the offspring's consumption, the effect of prenatal exposure to nicotine on the in utero development of these neurochemical systems would be expected to be stimulatory, rather than suppressive, in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal exposure to fat is found to stimulate the expression of these peptides in the hypothalamus and nucleus accumbens (Chang et al, 2008; Vucetic et al, 2010) and produce changes in the mesolimbic dopaminergic reward system (Naef et al, 2011; Ong & Muhlhausler, 2011; Vucetic et al, 2010) and in cholinergic activity in mesostriatal and hypothalamic areas (Morganstern et al, 2013). The possibility that these neurochemical changes in the offspring can, in turn, promote later consumption of nicotine is supported by pharmacological evidence in rats, showing that nicotine self-administration is reduced by hypothalamic administration of an OX receptor 1 antagonist or peripheral administration of an opioid antagonist (Ismayilova & Shoaib, 2010; LeSage, Perry, Kotz, Shelley, & Corrigall, 2010), by dopaminergic blockade through peripheral injection of receptor antagonists or lesions in the mesolimbic dopaminergic system (Corrigall & Coen, 1991; Corrigall, Franklin, Coen, & Clarke, 1992; Kutlu et al, 2013), and by systemic injection of a specific α7 nAChR antagonist, methyllycaconitine (Markou & Paterson, 2001). With additional evidence showing that nicotine injection can stimulate these orexigenic peptides and the dopaminergic and cholinergic systems (Houdi, Dasgupta, & Kindy, 1998; Loughlin et al, 2006; Rada, Jensen, & Hoebel, 2001), it is likely that nicotine self-administration and these neurochemicals function within a positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%